2019
DOI: 10.1038/s41380-019-0506-1
|View full text |Cite
|
Sign up to set email alerts
|

A POMC-originated circuit regulates stress-induced hypophagia, depression, and anhedonia

Abstract: Chronic stress causes dysregulations of mood and energy homeostasis, but the neurocircuitry underlying these alterations remain to be fully elucidated. Here we demonstrate that chronic restraint stress in mice results in hyperactivity of pro-opiomelanocortin neurons in the arcuate nucleus of the hypothalamus (POMC ARH neurons) associated with decreased neural activities of dopamine neurons in the ventral tegmental area (DA VTA neurons). We further revealed that POMC ARH neurons project to the VTA and provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 80 publications
5
84
4
1
Order By: Relevance
“…This anorectic effect was blocked by the MC4R antagonist. As stress increases the activity of ARC POMC neurons (Liu et al, 2007;Qu et al, 2020) and MC4Rs in the MeA contribute to stress-induced behavior and hypophagia (Liu et al, 2013), the ARC POMC →MeA pathway that we identified may contribute to stress-induced short-term hypophagia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This anorectic effect was blocked by the MC4R antagonist. As stress increases the activity of ARC POMC neurons (Liu et al, 2007;Qu et al, 2020) and MC4Rs in the MeA contribute to stress-induced behavior and hypophagia (Liu et al, 2013), the ARC POMC →MeA pathway that we identified may contribute to stress-induced short-term hypophagia.…”
Section: Discussionmentioning
confidence: 79%
“…It is known that fear and stress actively suppress eating. Chronic stress results in reduced body weight and anorexia that is associated with increased ARC POMC neuron activity (Qu et al, 2020 ). This anorectic effect in response to stress appears to be mediated through inhibition by opioids of dopamine-expressing neurons in the ventral tegmental area (VTA; Qu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ChR2-assisted circuit mapping. We performed the WGA-ChR2-assisted circuit mapping [46][47][48] in order to demonstrate the connectivity of ERα vlVMH neurons and their downstream target neurons in various brain regions. Briefly, 12-week-old Esr1-Cre female mice were anesthetized by isoflurane and received stereotaxic injections of Ad-iN/WED (200 nl, 6.1 × 10 12 VP per ml) and AAV-EF1α-DIO hChR2(H134R)-EYFP (200 nl, 6.2 × 10 12 VP per ml) into the vlVMH.…”
Section: Discussionmentioning
confidence: 99%
“…Primary study showed that the mice exhibited depression-like behavior when POMC neurons in the arcuate nucleus were inhibited. 24 Studies have pointed out that heroin addicts treated with intravenous diacetylmorphine could cause an POMC promoter methylation and reduce the level of stress hormone in the patient's body, thus playing a role in emotional regulation of treatment. 25 In alcohol dependence, POMC promoter methylation is associated with craving.…”
Section: Introductionmentioning
confidence: 99%